THE DIFFERENCES AND SIMILARITIES OF PROVERBS AND SAYINGS («СОВРЕМЕННЫЕ ФИЛОЛОГИЧЕСКИЕ ПАРАДИГМЫ: ВЗАИМОДЕЙСТВИЕ ТРАДИЦИЙ И ИННОВАЦИЙ», 2025)
Proverbs and sayings are two types of traditional expressions that have been used for centuries to convey wisdom, advice, and cultural norms. Both proverbs and sayings are typically short, easy-to-remember phrases that are used to make a point or to illustrate a truth.However, there are also some key differences between the two types of expressions. This study examined the differences and similarities between proverbs and sayings using a corpus of 100 proverbs and sayings. The study found that proverbs and sayings share a number of similarities.Both types of expressions are typically short, easy-to-remember phrases that are used to make a point or to illustrate a truth. Proverbs and sayings also often use figurative language, such as metaphors and similes.
Keywords: Proverbs, sayings, traditional expressions, wisdom, advice, cultural norms